Green economic development under the fiscal decentralization system: Evidence from china - Wang, Bingbing; Liu, Fengshuo; Yang, Siying (Frontiers in Environmental Science, 2022)
The literature is still divided on the study of the ecological and economic effects of fiscal decentralization. To clarify the relationship between fiscal decentralization between central and local governments and green economic development in developing countries, we take China as an example to test the impact of fiscal decentralization on green total factor productivity and its mechanism. It is found that fiscal decentralization helps local governments play a greater role in the regional economic system and promotes green economic development. From the perspective of policy synergy, environmental regulation is an enhanced mechanism for fiscal decentralization to promote green economic development. We also find that technological innovation is an important mechanism for fiscal decentralization to promote green economic development. Our study develops the theory of fiscal federalism and affirms the necessity of decentralization system reform in the context of the green economy, which has important theoretical and practical implications. Keywords: fiscal decentralization; green economy; environmental regulation; technological innovation